Te Reo Māori as a Subject: The Impact of Language Ideology, Language Practice, and Language Management on Secondary School Students’ Decision Making - Jeurissen, Maree (The Australian Journal of Indigenous Education, 2014)
Te reo Māori, the Indigenous language of Aotearoa (New Zealand), remains ‘endangered’ despite concentrated ongoing efforts to reverse declining numbers of speakers. Most of these efforts have focused on te reo Māori immersion education settings as these were considered the most effective means to ensure the survival of the language (May & Hill, 2008). More recently, the home has been identified as an important setting for language regeneration (Te Puni Kokiri, 2011). Despite the fact that the vast majority of secondary school-aged students (both Māori and non-Māori) attend English-medium schools, these settings are seldom considered as having potential to increase numbers of te reo Māori speakers. This article reports findings from a case study of one English-medium secondary school where factors surrounding the uptake of te reo Māori as a subject were investigated. Using Spolsky and Shohamy's (2000) language policy framework as an explanatory lens, it was revealed that even when students’ language ideologies orient them towards learning te reo Māori, language management and practice decisions can discourage rather than encourage this choice.